Career guidance in times of the pandemic - Sergeev, Igor [Verfasser] (My University, 2022)
"The challenge of the pandemic concerning career guidance turned out to be a serious problem since in recent years the emphasis has been on practice-oriented forms of work. Under these conditions, each region and each organization independently built a strategy for transform ing their career guidance work in the face of the pandemic. Only about one percent of those surveyed completely ceased career guidance activities. The pandemic did not so much exacerbate the problem of youth unemployment as it brought to light its specific characteristics. The period of remote learning showed that the vast majority of young people is not ready for productive self-study in a digital educational environment. Neither schools and colleges, nor universities prepare students for continuous, effective online self-education, despite such readiness becoming one of the leading requirements of modern employers, especially in the cutting-edge technology sectors." (Author's abstract ; BIBB-Doku)
Keywords: I 2.3.4 Asien; L 4.1.2 Elektronische Medien; 370; Berufsbildung; Pandemie; Arbeitsmarkt; Ausbildungsstellenmarkt; Russland; Digitale Medien; Selbstlernkompetenz